Case report: Inspiration from a rare fatal heart perforation after percutaneous vertebroplasty - Deng, Ke; Yu, Jia-Lin; Feng, Ye-Jun; Huang, Kui; Wu, Guo-Feng (Frontiers in Surgery, 2023)
The principal benefit of employing percutaneous vertebroplasty (PVP) for managing osteoporotic vertebral compression fractures lies in its capacity to facilitate early mobilization in elderly patients, thereby effectively avoiding the potential catastrophic complications associated with prolonged bedridden states. However, bone cement leakage, as the most common complication of PVP, may have fatal consequences.Here, we report a case involving an 85-year-old male patient with L1 vertebral compression fracture who underwent PVP at our hospital and was discharged on the same day of the surgical intervention. Subsequently, the patient experienced symptoms of chest tightness and palpitations. Cardiac ultrasound examination revealed pericardial effusion, while pulmonary computed tomographic angiography (CTA) demonstrated a strip high-density shadow in the right ventricular area. Finally, it was determined that the perforation of the right ventricular wall was caused by bone cement embolism. Through this comprehensive case report, we aim to deepen the understanding of orthopedic doctors on the importance of preventing bone cement leakage.